Revolution in Crisis: The Ruptures of Revolution and Ruptured Revolutions Through the Ruptures of Artistic Practice - Oliveira, Ana Balona de (2016)
This article proposes an investigation of the history and memory of the Carnation Revolution through the lens of contemporary art. Drawing upon the argument according to which history and memory are investigated by visual artists by means other, but no less relevant, than those of professional historians, this article will argue for the importance of attending to the visual, auditory, textual, object- and research-based ways in which artists from several generations and geographies have been unearthing the repressed histories and memories of the Carnation Revolution in Portugal and of anticolonial struggles, decolonization and post-independence nation-building in Mozambique, Guinea-Bissau and Angola. The discussion focuses on several works by Ângela Ferreira, but attention will also be paid to precursors in imaging the Revolution, such as Ana Hatherly, and to a younger generation of artists such as Filipa César, Kiluanji Kia Henda and Daniel Barroca.